Improvement of androgenetic alopecia with topical Sophora flavescens Aiton extract, and identification of the two active compounds in the extract that stimulate proliferation of human hair keratinocytes. (1st April 2016) - Takahashi, T.; Ishino, A.; Arai, T.; Hamada, C.; Nakazawa, Y.; Iwabuchi, T.; Tajima, M.
Summary: Background: Androgenetic alopecia (AGA) is a hair loss disorder that commonly affects middle‐aged men. To date, the properties of a number of natural or synthetic substances have been investigated for their ability to improve the condition. Aim: To evaluate the hair growth‐promoting activities of an extract from the root of Sophora flavescens Aiton. Methods: We used a human hair keratinocyte proliferation assay and ex vivo organ cultures of human hair follicle to examine the potential of the extract to stimulate hair growth via anagen elongation. We isolated the compounds promoting the growth of epithelial cells, and determined their chemical structures. A randomized, double‐blinded, placebo‐controlled clinical study for S. flavescens extract was carried out for 6 months with patients with AGA. Results: The extract stimulated the proliferation of hair keratinocytes at a concentration of 0.1 ng/mL, while 100 ng/mL of the extract had a marked effect on hair shaft elongation in an organ culture of human hair follicle. Cell proliferation assay‐directed fractionation led to the identification of two pterocarpan derivatives, L‐maackiain and medicarpin, as active compounds that promote the proliferation of human hair keratinocytes. Studies in human subjects showed that improvement in the inspected alopecia scores in the lotion plus extract group were significant over a period of 6 months ( P < 0.01). Conclusions: S. flavescens root extract is effective for the treatment of AGA. The isolated two pterocarpans might have important role in this effect.